Diurnal activity pattern of white-rumped vulture, Gyps bengalensis (Gmelin, 1788) in captivity during breeding season at Bangladesh National Zoo, Dhaka - Islam, Md Abraharul; Monirujjaman, -; Ahammed, Rasel; Aktar, Mahruma (Jahangirnagar University Journal of Biological Sciences, 2018)
Abstract not available Jahangirnagar University J. Biol. Sci. 7(1): 81-85, 2018 (June)